2022
DOI: 10.1155/2022/3723567
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Exerts Neuroprotective Effects via Autophagy Induction in C. elegans and Cellular Models of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a complex neurological disorder characterized by motor and nonmotor features. Although some drugs have been developed for the therapy of PD in a clinical setting, they only alleviate the clinical symptoms and have yet to show a cure. In this study, by employing the C. elegans model of PD, we found that ferulic acid (FA) significantly inhibited α-synuclein accumulation and improved dyskinesia in NL5901 worms. Meanwhile, FA remarkably decreased the degeneration of dopaminergic (DA) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Autophagy is a major proteolytic system responsible for the degradation of unwanted or misfolded proteins in eukaryotes (Wang & Le, 2019). Therefore, we investigated whether LCE induces autophagy in vivo using the transgenic C. elegans strain BC12921, which expresses the autophagy substrate protein SQST, homologous to the human P62 protein, in a stable manner (Long, Wu, et al, 2022). As shown in Figure 4a, both LCE and Rap (a positive autophagy inducer) significantly decreased the fluorescence intensity of SQST‐1/p62‐GFP in BC12921 worms, indicating the occurrence of autophagic flux in LCE‐treated worms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is a major proteolytic system responsible for the degradation of unwanted or misfolded proteins in eukaryotes (Wang & Le, 2019). Therefore, we investigated whether LCE induces autophagy in vivo using the transgenic C. elegans strain BC12921, which expresses the autophagy substrate protein SQST, homologous to the human P62 protein, in a stable manner (Long, Wu, et al, 2022). As shown in Figure 4a, both LCE and Rap (a positive autophagy inducer) significantly decreased the fluorescence intensity of SQST‐1/p62‐GFP in BC12921 worms, indicating the occurrence of autophagic flux in LCE‐treated worms.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we employed another C. elegans strain, DA2123, to validate the autophagy‐inducing activity of LCE. In DA2123 worms, the GFP::LGG‐1 fusion protein is sequestered at the membrane of autophagosomes and forms puncta when autophagy is triggered (Long, Wu, et al, 2022). We observed that LCE‐treated DA2123 worms exhibited higher numbers of LGG‐1 + puncta in seam cells and intestinal cells compared to untreated controls, where the fluorescence was diffused (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have shown that FA is a natural protective agent that requires further development. Ferulic acid exerts important neuroprotective effects in CNS diseases through antioxidant, anti‐inflammatory, anti‐apoptosis, alter gut microbiota and other mechanisms 110,111 . Moreover, FA was found to alleviate abnormal depressive behaviors in multiple animal depression models, underscoring the potential use of FA as a new antidepressant agent.…”
Section: Discussionmentioning
confidence: 99%
“…Long et al found that ferulic acid (concentrations between 25 and 200 μM, with 50 μM optimal) could ameliorate pathological changes in PD due to α-synuclein accumulation and the exposure of 6-OHDA and H 2 O 2 by activating autophagy in C. elegans and PC-12 cells, and that this protective effect was eliminated by inhibiting the autophagic activity of ferulic acid through feeding to RNAi bacteria, suggesting that ferulic acid may have considerable therapeutic application for PD through autophagy. 140 Another study discovered that caffeic acid (1−10 μM) might activate the JNK/Bcl-2-mediated autophagic pathway in SH-SY5Y cells, promoting the degradation of A53T-synuclein, and reducing cellular damage brought on by A53T-synuclein. 141 The JNK signaling pathway regulates autophagy primarily through phosphorylating Bcl2 family proteins and causing them to separate from Beclin-1.…”
Section: Autophagy Regulation By Hydroxycinnamic Acid Derivativesmentioning
confidence: 99%